Once versus twice daily enoxaparin for the initial treatment of acute venous thromboembolism - Trujillo-Santos J; Bergmann JF; Bortoluzzi C; López-Reyes R; Giorgi-Pierfranceschi M; López-Sáez JB; Ferrazzi P; Bascuñana J; Suriñach JM; Monreal M and the RIETE Investigators; Bosevski M; Zdraveska M (Thieme Medical Publishers, 2017)
Essentials In venous thromboembolism (VTE), it is uncertain if enoxaparin should be given twice or once daily. We compared the 15- and 30-day outcomes in VTE patients on enoxaparin twice vs. once daily. Patients on enoxaparin once daily had fewer major bleeds and deaths than those on twice daily. The rate of VTE recurrences was similar in both subgroups. Summary: Background In patients with acute venous thromboembolism (VTE), it is uncertain whether enoxaparin should be administered twice or once daily. Methods We used the RIETE Registry data to compare the 15- and 30-day rates of VTE recurrence, major bleeding and death between patients receiving enoxaparin twice daily and those receiving it once daily. We used propensity score matching to adjust for confounding variables. Results The study included 4730 patients: 3786 (80%) received enoxaparin twice daily and 944 once daily. During the first 15 days, patients on enoxaparin once daily had a trend towards more VTE recurrences (odds ratio [OR], 1.79; 95% confidence interval [CI], 0.55-5.88), fewer major bleeds (OR, 0.42; 95% CI, 0.17-1.08) and fewer deaths (OR, 0.32; 95% CI, 0.13-0.78) than those on enoxaparin twice daily. At day 30, patients on enoxaparin once daily had more VTE recurrences (OR, 2.5; 95% CI, 1.03-5.88), fewer major bleeds (OR, 0.40; 95% CI, 0.17-0.94) and fewer deaths (OR, 0.58; 95% CI, 0.33-1.00). On propensity analysis, patients on enoxaparin once daily had fewer major bleeds at 15 (hazard ratio [HR], 0.30; 95% CI, 0.10-0.88) and at 30 days (HR, 0.16; 95% CI, 0.04-0.68) and also fewer deaths at 15 (HR, 0.37; 95% CI, 0.14-0.99) and at 30 days (HR, 0.19; 95% CI, 0.07-0.54) than those on enoxaparin twice daily. Conclusions Our findings confirm that enoxaparin prescribed once daily results in fewer major bleeds than enoxaparin twice daily, as suggested in a meta-analysis of controlled clinical trials.
Keywords: bleeding; enoxaparin; mortality; recurrences; regimen; venous thromboembolism